Case report: unprecedented case of infantile cerebral infarction following COVID-19 and favorable outcome - Zheng, Shuhong; Chen, Hairui; Xu, Weiwei; Li, Haifeng; Chen, Zhongyu; Li, Jianhua; Tao, Enfu (Frontiers in Immunology, 2024)
The 2019 novel coronavirus, SARS-CoV-2, was highly prevalent in China as of December 2022, causing a range of symptoms, predominantly affecting the respiratory tract. While SARS-CoV-2 infection in children is generally mild, severe cases, especially in infants, are rare. We present a case of a previously healthy 7-month-old infant who developed cerebral infarction and coagulation dysfunction three days after COVID-19 onset. Clinically, the infant had weakness in the left limbs and pinpoint bleeding spots. A cranial magnetic resonance imaging showed ischemic strokes in the right basal ganglia and thalamus. Laboratory tests indicating thrombocytopenia and coagulation dysfunction. Inflammatory cytokines like interleukin-10 were elevated, with increased CD3 + , CD4 + , and CD8 + T lymphocytes but decreased CD3 -CD16 + CD56 + natural killer cells. Treatment included mannitol, dexamethasone, oral aspirin, and vitamins B1 and B6 for intracranial pressure, inflammation, anticoagulation, and nerve support, respectively. During the recovery phase, rehabilitation therapy focused on strength training, fine motor skills, and massage therapy. The infant gradually improved and successfully recovered. While rare, such cases can lead to severe complications. These combined efforts were instrumental in achieving significant functional recovery in the patient, demonstrating that even in severe instances of pediatric cerebral infarction due to COVID-19, positive outcomes are attainable with early and comprehensive medical response.